2022
DOI: 10.1177/00048674221107316
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk assessments: Why are we still relying on these a decade after the evidence showed they perform poorly?

Abstract: Suicide deaths have a profound impact on whānau and community and are a tragic loss. However, from a statistical point of view, suicide is a relatively rare event. Predicting rare events is difficult, and the implications for suicide prevention were highlighted in an important editorial in this journal more than a decade ago, yet little seems to have changed. Risk assessment that focuses on accurate prediction of suicide in real-world contexts is given a great deal of attention in mental health services, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Counselors used a structured approach to conversations about suicidality and self-harm behavior with the intention of focusing on intervention with the young person and not as a risk screening tool, in line with recent evidence [ 22 ]. Counselors had conversations about suicidality using a person-centered approach by listening, understanding, empathizing, and helping the young person find solutions they could connect with in a meaningful way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Counselors used a structured approach to conversations about suicidality and self-harm behavior with the intention of focusing on intervention with the young person and not as a risk screening tool, in line with recent evidence [ 22 ]. Counselors had conversations about suicidality using a person-centered approach by listening, understanding, empathizing, and helping the young person find solutions they could connect with in a meaningful way.…”
Section: Discussionmentioning
confidence: 99%
“…By having these conversations in a web-based, confidential environment, young people’s concerns about the consequences of disclosure in a face-to-face context can be minimized [ 45 ]. By moving away from risk assessment for the purpose of risk classification, the associated consequences of being classified in a certain way are removed, for example, being deemed low-risk and therefore not eligible for treatment [ 22 , 46 ]. LFT facilitated a real movement toward understanding the distress leading to suicidality and strategies to mitigate that distress instead of focusing on assessing the “risk” of future self-harm and suicide alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also spoke of using the likelihood of a student self‐harming or dying by suicide to determine how to respond. This is particularly concerning, given that research has clearly shown that the categorization of risk for prediction and treatment planning is futile and potentially harmful, with some receiving invasive and unhelpful treatment while others are left without support (Carter et al, 2017; Fortune & Hetrick, 2022; Graney et al, 2020; Kessler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%